Caring less about race: the prevalence of racial apathy among young adults - Sitterle, Daniel Key (Kansas State University, 2013)
In the wake of Barack Obama becoming the first nonwhite President of the United States and the diminishing instances of explicit racism, a number of Americans believe that the United States has surpassed race and therefore racism (Neville et al. 2000; Nayak 2006; Brayboy et al. 2007; Gawronski 2008; Quillian 2008; Wise 2009; Bonilla-Silva 2010; Gusa 2010; Ikuenobe 2010; Moras 2010; Gainous 2012). On the surface, the problem of overt racial discrimination has dramatically declined, yet, there are key studies that argue that new and subtler forms of racism are still prevalent (Feagin 2000; Krysan 2000; Sydell and Nelson 2000; Swim et al. 2003; Leach 2005; Henkel et al. 2006; Williams and Land 2006; Anderson 2007; D’Andrea and Daniels 2007; Sue et al. 2007; Gawronski et al. 2008; Wise 2009; Gainous 2012; Torres-Harding et al. 2012). This thesis will focus on assessing the dimensions of present-day racism and racial prejudice by replicating and updating Forman’s (2004) study of racial apathy. Using data from 2011 Monitoring the Future Survey, I explore the persistence of racial apathy, which proposes that the blatant racial discrimination of the past has manifested into racial indifference and lack of caring for existing racial inequalities (Perry and Shotwell 2009; Forman 2004; Forman and Lewis 2006; Gafford 2010; Maly et al. 2012). Consistent with previous research, this study finds that the expression of racial apathy has continued to increase, but also that political preference, gender, father’s education level and religiosity affect one’s level of racial apathy.
Keywords: Racial apathy; Race; Racism; Racial discrimination; Racial prejudice; Sociology (0626)